If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1 = -7 Reorder the terms: -1 + 3z = -7 Solving -1 + 3z = -7 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3z = -7 + 1 Combine like terms: -1 + 1 = 0 0 + 3z = -7 + 1 3z = -7 + 1 Combine like terms: -7 + 1 = -6 3z = -6 Divide each side by '3'. z = -2 Simplifying z = -2
| 2c+1=-5 | | y^2-16y+16=14 | | 9x-(4x+9)=3x-35 | | 60=6(2x-4) | | 3x^2+bx+1=0 | | 2k-1.2=3.6 | | Y=2(6)-13 | | -6+2p=1+3p | | P=B+3A | | 2x^2=300 | | 15y+3x=45 | | v=2+2 | | 9b-3=33 | | -6-7m=71 | | 23-9x+7x=21 | | 3+4y=y-8 | | 5=.33x | | 3h-6=15 | | Y=.33(0) | | Y=.33(-12) | | .25x-8=6 | | 9-10q=-6-7q | | 7/6-5/8=2 | | 10x^3-17x^2-6x= | | 5r+3=18 | | 5x+7=-127 | | -5=-y+2 | | 4x-5y=-8 | | -b=-8+b | | 5x-7=-127 | | X=-0+2 | | (3)=-7x |